CLINICAL AND ANAMNESTIC FEATURES OF THE COURSE OF SEVERE PNEUMONIA IN EARLY AGE CHILDREN WITH CONGENITAL ANOMALIES OF CLEFT LIP AND PALATE (Modern education and development, 2025)
In this study, clinical and anamnestic features of the course of severe pneumonia in early age children with congenital anomalies of the cleft lip and palate were observed with analysing of life history and current condition of the children. Research methods are analysis, clinical observations, x-ray studies. Clinical and anamnestic features of the course of severe pneumonia in early age children with congenital anomalies of the cleft lip and palate were determined. It was revealed that the severity of the condition of examined children was due to a burdened maternal history, premorbid background, artificial feeding and prematurity factor itself and such conditions of the microflora of the gastrointestinal tract.